Essentials of Stem Cell Biology - Lanza, Robert P;Ed. Gearhart, John P;Ed (Elsevier Academic Press, 2006)
Following the advances in stem cells, including full color presentation throughout, this two-volume set combines the prerequisites for a general understanding of adult and embryonic stem cells; and the tools, methods, and experimental protocols needed to study and characterize stem cells and progenitor populations